Chronic administration of catalase inhibitor attenuates hypertension in renovascular hypertensive rats - Lauar, Mariana R. [UNESP]; Colombari, Débora S.A. [UNESP]; De Paula, Patrícia M. [UNESP]; Colombari, Eduardo [UNESP]; Andrade, Carina A.F. [UNESP]; De Luca, Laurival A. [UNESP]; Menani, José V. [UNESP] (Elsevier, 2023)
Aims: Reactive oxygen species like hydrogen peroxide (H2O2) are produced endogenously and may participate in intra- and extracellular signaling, including modulation of angiotensin II responses. In the present study, we investigated the effects of chronic subcutaneous (sc) administration of the catalase inhibitor 3-amino-1,2,4-triazole (ATZ) on arterial pressure, autonomic modulation of arterial pressure, hypothalamic expression of AT1 receptors and neuroinflammatory markers and fluid balance in 2-kidney, 1clip (2K1C) renovascular hypertensive rats. Materials and methods: Male Holtzman rats with a clip occluding partially the left renal artery and chronic sc injections of ATZ were used. Key findings: Subcutaneous injections of ATZ (600 mg/kg of body weight/day) for 9 days in 2K1C rats reduced arterial pressure (137 ± 8, vs. saline: 182 ± 8 mmHg). ATZ also reduced the sympathetic modulation and enhanced the parasympathetic modulation of pulse interval, reducing the sympatho-vagal balance. Additionally, ATZ reduced mRNA expression for interleukins 6 and IL-1β, tumor necrosis factor-α, AT1 receptor (0.77 ± 0.06, vs. saline: 1.47 ± 0.26 fold change), NOX 2 (0.85 ± 0.13, vs. saline: 1.75 ± 0.15 fold change) and the marker of microglial activation, CD 11 (0.47 ± 0.07, vs. saline, 1.34 ± 0.15 fold change) in the hypothalamus of 2K1C rats. Daily water and food intake and renal excretion were only slightly modified by ATZ. Significance: The results suggest that the increase of endogenous H2O2 availability with chronic treatment with ATZ had an anti-hypertensive effect in 2K1C hypertensive rats. This effect depends on decreased activity of sympathetic pressor mechanisms and mRNA expression of AT1 receptors and neuroinflammatory markers possibly due to reduced angiotensin II action.
Keywords: Angiotensin II; Autonomic modulation; Catalase inhibitor; Hydrogen peroxide; Hypertension; Neuro-inflammation; Sympathetic activity